AMZ Industries: Managing family business, what’s next? - Fakhrul Anwar, Zainol; Nalini, Arumugam; Asmahani, Ibrahim; Norhayate, Wan Daud (2014)
AMZ Industries (also known as AMZ) is one of the pioneer company in the furniture production industry in Kuala Terengganu, Terengganu, Malaysia. Interestingly, AMZ has joined by skilled personnel and it also has the latest technology in manufacturing processes that meet stringent guidelines set by international standard. The Germany Board Certification has recognized ABC as one of the manufacturers that has superior quality system. From the beginning of its inception, the industry grew to become the 1st choice among their clients. A unique combination of offering quality products and affordable prices to the clients is working well. The company also doesn’t have problems hold a mass production line as requested by clients as they have enough capacity to achieve it. Despite its success AMZ has faced several challenges that have not only affected the management, but also its business operation. This case study will look at the operational challenges and several issues faced by AMZ, internally and externally in the context of family business in small medium enterprises (SMEs) in Malaysia.